Aspects of Vietnamese Sutchi Catfish (Pangasius Hypophthalmus) Frozen Fillet Quality: Microbiological Profile and Chemical Residues. Issue 4 (17th March 2016) - Dambrosio, Angela; Normanno, Giovanni; Storelli, Arianna; Barone, Grazia; Ioanna, Federica; Errico, Luigi; Centoducati, Gerardo; Storelli, Maria M.
Abstract: Pangasius hypophthalmus fillets, classified according to different frozen technologies, were subjected to microbiological (Psychrophilic Total Aerobic Count = PTAC, Enterobacteriacea, Staphylococcus aureus, Salmonella spp. and Listeria monocytogenes ) and chemical analyses (Hg, Pb, Cd and six "indicator" congeners of polychlorinated biphenyls=PCB6 ). Mean count of psychrophilic aerobic total bacteria, Enterobacteriaceae and S. aureus in all samples examined was 4.44 log CFU/g, 2.16 log CFU/g and 1.07 log CFU/g, respectively. Any sample showed the presence of Salmonella, while L. monocytogenes was encountered in 2.1% of samples tested. The microbiological counts were different among fillet categories, but with values always lower than the limit of ICMSF. Also the chemical quality of processed products is satisfactory being the concentrations of all metals and six "indicator" PCBs below safety levels for human consumption. This study has contributed to addressing the current paucity in literature on the microbial and chemical status of frozen P. hypophthalmus fillets. Practical Applications: The present research reveals a good chemical and microbiological quality of the frozen Pangasius fillets, although the samples examined show a low incidence of Listeria monocytogenes and Staphylococcus aureus . Thus, it would be desirable a greater attention to the operator's personal hygiene practices during the processing procedures, appropriate preservation techniques and sanitation programs in the processing plants to avoid cross‐contamination. The data contained in this study may also be useful for national and international food safety regulatory authorities.